Digestibility of wheat grain dual purpose, BRS Tarumã cultivar, produced in agroecological or conventional system for pigs Digestibilidade do grão de trigo de duplo propósito, cultivar BRS Tarumã, produzido em sistema agroecológico ou convencional para suínos - Nantes C.L. (2014)
Three experiments of the digestibility were carried out to determine the nutritional value, apparent digestibility and metabolizable coefficients and energy values for dual purpose wheat (BRS Tarumã) produced in agroecological or conventional system, for pigs in different stages (15, 45 and 75 kg of body weight-BW). Were used 15 barrows crossbreed of the commercial high-performance hybrids for each phase, allotted in three experimental groups, the first group received a diet specific to stage, called basal diet (BD) the other groups received diet with 70% RR and 30% of dual-purpose wheat agroecological (Group 2) or conventional (Group 3). Were evaluated differences between the coefficients for each phase of the study. For the differences between phases were used descriptive analyzes. Production systems (conventional and agroecological) not affect the digestibility of wheat. The mean digestibility coefficients at 45 and 75 kg were higher. The digestible energy values were 3.25, 3.56 and 3.59 Mcal/kg for conventional and 3.14, 3.45 and 3.57 Mcal/kg for agroecological wheat for phases 15, 45 and 75 kg of BW, respectively. The use of wheat from the stage 45 kg showed better digestibility values, regardless of the production system.